Finding multi-constrained path using genetic algorithm - Yussof S.; See O.H. (2023)
To properly support networked multimedia applications, it is important for the network to provide quality-of-service (QoS) guarantees. One way to provide QoS guarantees is for the network to perform QoS routing, where the path taken must fulfill certain constraints. Multi-constrained path (MCP) problem refers to the problem of finding a path through a network subject to multiple additive constraints. It has been proven that this problem is NP-complete and therefore no exact algorithm can be found. As such, various heuristics and approximation algorithms have been proposed to solve the MCP problem. This paper presents a solution to the MCP problem using genetic algorithm (GA). Through simulation, this algorithm has been shown to give a high probability of finding a feasible path if such paths exist. 2007 IEEE.